Distribution of the eggs of defoliating Lepidoptera (Noctuoidea) in soybean plants and its relation to crop phenology - Valverde, Liliana; Virla, Eduardo; Van Nieuwenhove, Guido (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
Soybean is a strategic crop for the economy of several South American countries. Phytophagous Lepidoptera are an important taxon affecting crop yield, being Anticarsia gemmatalis (Hübner) (Erebidae: Eulepidotinae), Rachiplusia nu (Guenée) and Chrysodeixis includens (Walker) (Noctuidae: Plusiinae) their main pests in Subtropical region of South America. The objectives of this study were to determine the location in field of eggs of Lepidoptera Noctuids in different organs of the soybean plant and its abundance and distribution in the plants considering the growth stage of the crop. Samples were taken weekly during three crop seasons, on a plot of 80 ha of soybean managed with conventional farming practices. The identification of lepidopteran eggs was performed following specific keys. More than 90% of eggs of the three defoliating species are deposited in the folioles, and especially in those located on the middle and upper level of the plants. Throughout the development of the crop, the highest densities of eggs were recorded in early stages (vegetative and flowering) being less abundant at fruiting. The study of the egg distribution of these pest species at the plant provides necessary information to establish preventive strategies for their control.